Exercise interventions for the prevention of depression: a systematic review of meta-analyses - Mandy X. Hu; David Turner; Ellen Generaal; Daniel Bos; M. Kamran Ikram; M. Arfan Ikram; Pim Cuijpers; Brenda W. J. H. Penninx (BMC, 2020)
Abstract Background Exercise may be a promising target for depression interventions. However, evidence for a beneficial effect of exercise interventions on the prevention of depression differs substantially across different studies. Methods A systematic search was performed up to July 2018 using PubMed, Embase, PsycINFO, and Cochrane. Articles were included if a meta-analysis of randomized controlled trials was performed that examined the effect of exercise interventions on the onset of depression or depressive symptoms in the general population. Meta-analyses focusing on treatment of diagnosed depression were excluded. Two authors independently screened the articles and graded the quality of included meta-analyses using AMSTAR 2. Results Eight meta-analyses were included that showed little overlap in 134 included studies. All meta-analyses reported on depressive symptoms rather than onset of depression. Five of these were rated as moderate quality and three of low quality. Six meta-analyses found significant effects, and two found non-significant effects of exercise interventions in reducing depressive symptoms in children, adolescents, adults and the elderly (effect sizes ranging from − 0.10 to − 0.81). Scarce evidence did not allow to draw conclusions about the role of sex and characteristics of exercise on depression. However, some findings suggest that low intensity exercise was as effective as high intensity exercise. Heterogeneity among primary studies was high, likely caused by differences in study quality and exercise characteristics. Conclusions The evidence from this study suggests that exercise interventions have a beneficial effect on depressive symptoms in the general population across a wide age-range.